Field notes contributed by Thomas H. Kent, winter 1981-1982 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
Field notes were contributed by Thomas H. Kent and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed